2004
DOI: 10.1128/jb.186.22.7499-7507.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Zinc Transport by Two Bacterial Cation Diffusion Facilitators from Ralstonia metallidurans CH34 and Escherichia coli

Abstract: CzcD from Ralstonia metallidurans and ZitB from Escherichia coli are prototypes of bacterial members of the cation diffusion facilitator (CDF) protein family. Expression of the czcD gene in an E. coli mutant strain devoid of zitB and the gene for the zinc-transporting P-type ATPase zntA rendered this strain more zinc resistant and caused decreased accumulation of zinc. CzcD, purified as an amino-terminal streptavidin-tagged protein, . Conserved amino acyl residues that might be involved in binding and transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 31 publications
9
108
0
1
Order By: Relevance
“…The mean values of the data from at least three independent experiments were used to determine the 50% inhibitory concentration (IC 50 ) values, which are the concentrations required to diminish cell density by 50% under the conditions tested. The formula used was the simplified version OD(c) ϭ OD 0 /(1 ϩ exp[(c Ϫ IC 50 )/b)] of a Hill-type equation as introduced by Pace and Scholtz (52) and described previously (5). OD(c) is the turbidity at a given metal concentration, OD 0 is that at no added metal, b is the slope of the sigmoidal dose response curve, and c is the metal concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The mean values of the data from at least three independent experiments were used to determine the 50% inhibitory concentration (IC 50 ) values, which are the concentrations required to diminish cell density by 50% under the conditions tested. The formula used was the simplified version OD(c) ϭ OD 0 /(1 ϩ exp[(c Ϫ IC 50 )/b)] of a Hill-type equation as introduced by Pace and Scholtz (52) and described previously (5). OD(c) is the turbidity at a given metal concentration, OD 0 is that at no added metal, b is the slope of the sigmoidal dose response curve, and c is the metal concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Members of this family belong to the larger group of cation diffusion facilitator (CDF) proteins and are primarily involved in metal ion transport (5). ClustalW sequence analysis of the promoter region predicted a region with 58% identity to the E. coli Fur box consensus sequence (57).…”
Section: Vol 76 2008 Role Of Iron-regulated Genes In C Burnetii Pamentioning
confidence: 99%
“…Both Zn 2ϩ and Fe 2ϩ are borderline soft metal ions with a similar donor preference for a combination of three protein ligand groups as follows: the cysteine thiolate, histidine imidazole, and aspartate/glutamate carboxylate (16). Phenotype analyses of two homologous CDF transporters, CzcD from Ralstonia metallidurans and ZitB from E. coli, demonstrated that mutating a highly conserved Asp residue in the putative TM-5 rendered host cells hypersensitive to zinc, probably because of a loss of zinc efflux pumping activities (17). The Asp appeared to be essential because expression of CzcD D158E , CzcD D158A , ZitB D163E , and ZitB D163A mutant proteins conferred no zinc resistance.…”
mentioning
confidence: 99%